Sewa Menyewa Jasa Bajak Sawah Perspektif Hukum Islam: Studi Kasus Desa Pakikiran, Banjarnegara - Farida Isnaeni; Syifaun Nada; Juen (Fakultas Syariah UIN Prof. K.H. Saifuddin Zuhri, 2024)
An agreement on a wage payment system that is undertaken by musta’jīr in cash with payment when the rice fields are plowed after being plowed. However, in practice, many parties must not pay directly the wages that must be musta’jīr. This happened due to the inability of musta’jīr caused by the transfer of capital for planting and maintenance costs. Delay in paying wages raises injustice and losses for one party. In fact, the ijarāh contract contains the principle of justice by avoiding the element of loss for one of the parties. So this research is important to be carried out, with this research it is hoped that it will be able to bring benefits, not only to one party but to all parties involved in the contract. This research is a field research that directly seeks information from the public. By conducting observations, interviews and documentation. The primary data source used is in the form of informants who have made rental transactions at rice plow services in Pakikiran Village, namely from service providers, tractor owners and farmers. The results of this study show that the practice of renting rice plow services that occurs in Pakikiran Village has occurred since the 90s. In responding to the delay in wage payment, the people of Pakikiran Village refer to the principle of helping each other. Because even though there are parties who are harmed, on the other hand there are parties who must be helped because of their inability to pay the wages directly, because the payment of wages for rice plow services is diverted to planting costs to avoid damage in the form of crop failure and also crop failure. It has become a habit of the local community so that economic activities always bring benefits. Based on the study of existing Islamic law, even though there are delays in the wage payment system. However, the delay is forgiven because it is a good community custom and does not contradict Islamic law.